Human immunodeficiency virus pretreatment drug resistance to first line antiretroviral therapy: a single center study - Okasha, Hadir; Afifi, Amany Refaat; Ibrahim, Khaled Ibn-Elwalid; Emad, Rasha; Alzahaby, Amgad A.; Abdel-Baki, Amin; Goumaa, Ramadan; Amer, Amira Fathy (The Egyptian journal of internal medicine, 2025)
Background Human immunodeficiency virus (HIV) infection is a worldwide health problem that contributes to hundreds of thousands of deaths each year. In Egypt, all infected people are offered treatment on diagnosis, free of charge, regardless of the CD4 count or the viral load. Resistance of HIV to antiretroviral therapy (ART) is a rising problem that faces healthcare providers and necessitates increasing efforts to counter its effects. Consequently, the World Health Organization (WHO) recommends surveillance of pretreatment drug resistance (PDR) present before treatment initiation and acquired drug resistance (ADR) developed during therapy. Our study aimed to discover the prevalence of PDR to nucleoside reverse transcriptase inhibitors (NRTIs) and non-nucleoside reverse transcriptase inhibitors (NNRTIs) in Alexandria and to identify the predominant circulating HIV strain in the governorate. Methods This is a cross-sectional study that was conducted in Alexandria Fever Hospital during a six-month period. Plasma samples were collected from patients who were treatment-naïve and initiating therapy, as well as from patients reinitiating therapy after a cessation period exceeding three months. Samples with a viral load exceeding 1000 copies/ml were subjected to sequence analysis of the reverse transcriptase (RT) gene. Generated sequences were analyzed using the Stanford HIV Drug Resistance Database, and drug resistance mutations were identified, and PDR was determined. Results Pretreatment drug resistance (PDR) to either NRTIs, NNRTIs, or both was detected in 17.3% of samples. PDR was significantly more prevalent among ART reinitiators, with 50% of reinitiators' samples carrying resistance-conferring mutations, all of which were to NNRTIs. In contrast, only 11.4% of the samples from ART initiators exhibited similar mutations. Subtyping of the studied cases, based on sequence analysis using the Stanford HIV drug resistance database, revealed that Circulating Recombinant Form (CRF02_AG) was the most prevalent subtype, accounting for 55.8% of studied strains, followed by subtype B detected in 15.4% of samples. Conclusions Our findings suggest a concerning level of resistance to reverse transcriptase inhibitors, particularly among reinitiators of ART. The study also found that CRF02_AG is the most prevalent HIV strain among the study subjects.